Vulvar lichen sclerosus et atrophicus - Pragya Ashok Nair (Wolters Kluwer Medknow Publications, 2017)
Vulvar lichen sclerosus (VLS) is a chronic inflammatory dermatosis characterized by ivory-white plaques or patches with glistening surface commonly affecting the vulva and anus. Common symptoms are irritation, soreness, dyspareunia, dysuria, and urinary or fecal incontinence. Anogenital lichen sclerosus (LS) is characterized by porcelain-white atrophic plaques, which may become confluent extending around the vulval and perianal skin in a figure of eight configuration. Thinning and shrinkage of the genital area make coitus, urination, and defecation painful. LS is not uncommon in India and present as an itchy vulvar dermatosis which a gynecologist may mistake for candidal vulvovaginitis. There is often a delay in diagnosis of VLS due to its asymptomatic nature and lack of awareness in patients as well as physicians. Embarrassment of patients due to private nature of the disease and failure to examine the genital skin properly are the other reasons for delay in diagnosis. There is no curative treatment for LS. Various medications available only relieve the symptoms. Chronic nature of the disease affects the quality of life. Proper and regular follow-up is required as there are chances of the development of squamous cell carcinoma.